A detailed surface characterization study of SBA-15 and B-SBA-15-x mesoporous materials using the IGC technique. (October 2022) - Yarbaş, Tuğba; Çıtak, Alime
Abstract: Pure and boron-containing B-SBA-15-x (molar ratio, Si/B = 50, 30, 10) mesoporous materials were synthesized by a direct hydrothermal procedure. Samples were characterized by XRD, ICP-OES, FT-IR, BET and SEM. Inverse gas chromatography (IGC) technique was used to determine the dispersive surface energies ( γ S d ), adsorption thermodynamic parameters (ΔH, ΔG, ΔS) and the acid-base constants (KA and KD ) of the samples. IGC experiments were performed at infinite dilution region at 200, 210, 220 and 230 °C. The surface characterization results confirmed that the SBA-15 structure was formed, boron was added to the structure and all samples have meso pores. The surface area of the pure SBA-15 was determined as 745.288 m 2 /g and it was found that the surface area decreases with increasing boron content. Physical adsorption occurred between the IGC probe molecules and all SBA-15 materials according to the adsorption thermodynamic parameters. ( γ S d ) values of pure SBA-15, B-SBA-15-50, B-SBA-15-30 and B-SBA-15-10 were found at 40.873, 37.039, 36.636 and 37.444 mJ/m 2 at 200 °C, respectively. It has been observed that the dispersive surface energy of all samples decreases with increasing temperature. According to the SC value calculated from the KA and KD parameters, the surface of B-SBA-15-10 with the highest boron content was found to be acidic. On the other hand the surfaces of all other samples were determined as basic.